The effect of the inverted learning strategy on the achievement of second-grade secondary school students in the history subject - Hameed Wadi, Hiba (International Journal of Psychosocial Rehabilitation, 2020)
Because of the development that has taken place in all aspects of the twentieth century, educational systems do not only teach learners various sciences, such as social studies, through investing mental phases for educational stages and setting educational programs. These programs work on developing various mental skills and capabilities such as awareness, attention, focus, and the ability to think properly. Investing in minds is the logical investment in all societies to prepare people who are able to face the changes of life and its requirements, so institutions concerned focus on developing mental capabilities. In the light of the above discussion, the researcher, through her experience in the field of teaching, her knowledge of literature and studies, and consulting the opinions of some male and female teachers of social subjects in general and history in particular, notices that some methods of implementing the lesson depend on the experience of the school or the academic teacher. This experience does not suit the capabilities and qualifications of the students. This makes the learners receptive and obedient to the teacher’s orders without providing sufficient opportunities to develop their abilities and skills, such as thinking. Therefore, the current research problem is represented by the urgent need to improve these methods and the use of modern models and strategies in teaching. The problem also lies in the weak validity of the teaching methods used that were indicated by the results of the survey study. In the light of those justifications and rationales, the current research problem takes shape in answering the following question (what are the effects of a flipped learning strategy on the achievement of second-graders average in the history subject?).